The petrosal bone and bony labyrinth of early to middle Miocene European deer (Mammalia, Cervidae) reveal their phylogeny. (26th July 2016) - Mennecart, Bastien; Rössner, Gertrud E.; Métais, Grégoire; DeMiguel, Daniel; Schulz, Georg; Müller, Bert; Costeur, Loïc
ABSTRACT: Deer (Cervidae) have a long evolutionary history dating back to the Early Miocene, around 19 million years ago. The best known fossils to document this history belong to European taxa, which all bear cranial appendages more or less similar to today's deer antlers. Despite the good fossil record, relationships of the earliest stem deer and earliest crown deer are much debated. This hampers precise calibration against the independent evidence of the fossil record in molecular clock analyses. While much has been written on the Early and Middle Miocene deer, only two phylogenetic analyses have been performed on these taxa to date mostly based on cranial appendage characters. Because the petrosal bone and bony labyrinth have been shown to be relevant for phylogeny in ruminants, we describe for the first time these elements for four iconic early cervids from Europe ( Procervulus dichotomus, Heteroprox larteti, Dicrocerus elegans and Euprox furcatus ) and include them in a phylogenetic analysis based on the ear region exclusively. The analysis recovered E. furcatus in a sister position to the living red deer ( Cervus elaphus ). Further, it placed D. elegans in a sister position to Euprox  +  Cervus and a clade Procervulinae that includes P. dichotomus and H. larteti, in sister position to all other deer. The inclusion of E. furcatus in crown Cervidae, which was previously suggested based on antler morphology, cannot be ruled out here but needs a more comprehensive comparison to other crown deer to be confirmed. J. Morphol. 277:1329–1338, 2016. © 2016 Wiley Periodicals, Inc.